Managing Gut Microbiota through In Ovo Nutrition Influences Early-Life Programming in Broiler Chickens - Abdelrazeq M. Shehata; Vinod K. Paswan; Youssef A. Attia; Abdel-Moneim Eid Abdel-Moneim; Mohammed Sh. Abougabal; Mohamed Sharaf; Reda Elmazoudy; Wejdan T. Alghafari; Mohamed A. Osman; Mayada R. Farag; Mahmoud Alagawany (Animals, 2021)
The chicken gut is the habitat to trillions of microorganisms that affect physiological functions and immune status through metabolic activities and host interaction. Gut microbiota research previously focused on inflammation; however, it is now clear that these microbial communities play an essential role in maintaining normal homeostatic conditions by regulating the immune system. In addition, the microbiota helps reduce and prevent pathogen colonization of the gut via the mechanism of competitive exclusion and the synthesis of bactericidal molecules. Under commercial conditions, newly hatched chicks have access to feed after 36–72 h of hatching due to the hatch window and routine hatchery practices. This delay adversely affects the potential inoculation of the healthy microbiota and impairs the development and maturation of muscle, the immune system, and the gastrointestinal tract (GIT). Modulating the gut microbiota has been proposed as a potential strategy for improving host health and productivity and avoiding undesirable effects on gut health and the immune system. Using early-life programming via in ovo stimulation with probiotics and prebiotics, it may be possible to avoid selected metabolic disorders, poor immunity, and pathogen resistance, which the broiler industry now faces due to commercial hatching and selection pressures imposed by an increasingly demanding market.